Best friends for never : a Clique novel - Harrison, Lisi (Little, Brown, 2004)
A bet about wardrobes between the wealthy Massie and middle-class Claire results in a testing of old friendships, a forging of new ones, and a change for the student body at Octavian Country Day School.